Peningkatan Kinerja Pegawai Sebagai Konsekuensi dari Tingkat Pendidikan, Kompetensi, Lingkungan Kerja, Disiplin Kerja, dan Kompensasi - Maman Sulaeman; Hima Barima (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2022)
The State Civil Apparatus (ASN) is a professional group for employees who work in central government agencies and local governments. ASN performance assessment is conducted to ensure the objectivity of ASN coaching based on the achievement system and career system. The purpose of this study is to find out the influence of the level of education; competence; work environment; discipline of work; and compensation for the performance of the ASN of the Purbalingga Regency Regional Secretariat. Research methods use quantitative methods. Data retrieval techniques using surveys. The instrument used is a questionnaire. The results showed that the level of education, competence, work environment, compensation and work discipline had a positive effect on employee performance